PENINGKATAN PENALARAN MATEMATIKA MELALUI STRATEGI THINK PAIR SHARE BERBASISPROBLEM BASED LEARNING(PTK pada Siswa Kelas X Multimedia B Semester Genap SMK Negeri 9 Surakarta Tahun 2016/ 2017) - Maimunnah, Tsaniatu (2017)
The purpose of this research is to increase mathematical reasoning for X grade students Multimedia B SMK Negeri 9 Surakarta through think pair share strategy based problem based learning. This type of research is a classroom action research. The subjects who give the action in this research is the teacher and the subject of the action recipients are students of X grade Multimedia B SMK Negeri 9 Surakarta which have 32 students, consisting of 17 male students and 15 female students. The implementation of a class action was conducted in two cycles consisting of two meetings. Technique of collectingdata conducted with using observation, test methods, field notes, and documentation. Technique of analysis data was using reduction, data presentation, and conclusion. The validity of the data used investigation triangulation techniques. The results of the research showed there was increasing of mathematical reasoning is based on several indicators, there were: (1) students who are able to serve mathematical declaration with spoken was 12.5% before the action research and 63% after giving the action research, (2) students who are able to give a reason / evidence of the truth of solution showed 31.25% and changes to 70% after the action research, (3) students who are able to pull the conclusion before action research was 8% and increasing to 66.67%.